Internet addiction: reappraisal of an increasingly inadequate concept - Starcevic, Vladan; Aboujaoude, Elias (CNS spectrums, 2017)
This article re-examines the popular concept of Internet addiction, discusses the key problems associated with it, and proposes possible alternatives. The concept of Internet addiction is inadequate for several reasons. Addiction may be a correct designation only for the minority of individuals who meet the general criteria for addiction, and it needs to be better demarcated from various patterns of excessive or abnormal use. Addiction to the Internet as a medium does not exist, although the Internet as a medium may play an important role in making some behaviors addictive. The Internet can no longer be separated from other potentially overused media, such as text messaging and gaming platforms. Internet addiction is conceptually too heterogeneous because it pertains to a variety of very different behaviors. Internet addiction should be replaced by terms that refer to the specific behaviors (eg, gaming, gambling, or sexual activity), regardless of whether these are performed online or offline.